2010
DOI: 10.1108/09596111011066644
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice, employees' ethical behavior, and job satisfaction in the casino industry

Abstract: Purpose -The paper aims to examine the antecedents and consequence of casino employees' ethical behavior. In particular, it proposes that both distributive and procedural justice have positive influences on such behavior, which in turn positively affects workers' job satisfaction. The paper aims to help casino management pinpoint areas for enhancing and promoting employees' ethical behavior so as to benefit industry stakeholders. Design/methodology/approach -A questionnaire was designed based on a literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 48 publications
3
54
0
3
Order By: Relevance
“…Third, a careful examination of the hospitality management literature indicates that there are a number of studies that have examined factors influencing job, career, or life satisfaction (e.g., Kara et al, 2012;McCain et al, 2010;Yang, 2010). However, the preponderance of these studies has used one or at most two forms of satisfaction (Yavas et al, 2013).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Third, a careful examination of the hospitality management literature indicates that there are a number of studies that have examined factors influencing job, career, or life satisfaction (e.g., Kara et al, 2012;McCain et al, 2010;Yang, 2010). However, the preponderance of these studies has used one or at most two forms of satisfaction (Yavas et al, 2013).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Leaders exhibiting post-conventional moral reasoning are inclined to use TFL behavior and are perceived as such by the subordinates (Trevino, 1986;Turner et al, 2002). Ethical reasoning is not the only barometer to measure moral development as they are varieties of models (Chen McCain, Tsai, & Bellino, 2010). This adds value and increased our understanding of both concepts as it will guide leadership training tailor measured to suit the realities on the ground.…”
Section: Resultsmentioning
confidence: 99%
“…Equitable rewards are reported as important motivators to employees (Cloinger et al, 2011;McCain et al, 2010;Milkovich et al, 2010). Adams's (1965) equity theory suggested that if individuals perceive that their performance is not rewarded on an equitable basis, they may reduce their efforts and performance, or even leave the company.…”
Section: Consequences Of Perceived Equity and Work Attitudes And Behamentioning
confidence: 99%